Characterization of de novo colonic stricture due to Crohn’s disease - Başaranoğlu, Metin; Sayılır, Abdurrahim; Yüksel, Mahmut; Yıldız, Hakan; Suvak, Burak; Turhan, Nesrin; Tunç, Bilge; Özin, Yasemin (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The development of colonic stenosis is a rare complication of Crohn’s disease (CD) without a surgical anastomosis history. So, the management and long-term follow-up results of colonic stricture due to CD have not been clearly defined. In this study, we aimed to characterize de novo colonic stricture due to CD. Materials and Methods: We evaluated 702 patients with CD to investigate colonic stricture. Colonic stricture was considered to exist when passage of a standard colonoscope was not possible and was diagnosed radiologically and endoscopically in this study. Results: Of the 702 patients, 14 had colonic stricture according to the definition above. Of the 14, 8 were male. The interval between diagnosis of disease and recognition of the stricture varied from 0 to 13 years. Localization of the strictures differed from the rectum to cecum. Of the 14, 3 patients had more than 1 stricture. Pathological examination of the stricture(s) did not show dysplasia or malignancy initially or during the follow-up. Conclusion: De novo colonic stricture due to CD is a rare condition according to the presented study’s results. Distribution of the stricture(s) varied from the rectum to cecum without increased colonic cancer risk. We observed the antifibrotic role of thiopurines and biologic agents in this study.